High-throughput screening of multimetallic catalysts for three-way catalysis - Son Dinh Le; Nhan Nu Thanh Ton; Kalaivani Seenivasan; Patchanee Chammingkwan; Koichi Higashimine; Supareak Praserthdam; Toshiaki Taniike (Science and Technology of Advanced Materials: Methods, 2024)
Multimetallic nanoparticles (MNPs) have appeared as promising catalysts for important catalytic reactions such as three-way catalysis (TWC) due to their synergistic effects. Herein, a comprehensive process of preparing and evaluating MNPs and supported catalysts using high-throughput experimentation (HTE) for TWC is demonstrated. The synthesis of MNPs via a hot-injection method is performed using a homemade parallel reactor. The prepared MNPs are impregnated in parallel on alumina and examined for TWC. An in-house fixed-bed reactor equipped with a quadrupole mass spectrometer was employed for catalyst evaluation, taking advantage of the rapid screening of 20 catalysts and multiple reaction conditions. The overall HTE system can facilitate the synthesis and evaluation of 51 multimetallic catalysts for TWC in less than 2 weeks, and also appear to be a flexible and versatile system for other applications.